THE CORRELATION BETWEEN CRYSTALLOID FLUID PRELOADING AND BLOOD PRESSURE IN PATIENTS UNDERGOING CESAREAN SECTION WITH SPINAL ANESTHESIA AT THE CENTRAL SURGICAL INSTALLATION - Aurelia Anaya Dwi Pradianita; Nurul Fatwati Fitriana; Marta Tania Gabriel Ching Cing; Tati Hardiyani (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Spinal anesthesia for cesarean section often causes maternal hypotension in 60-70% of cases, so an effective fluid management strategy is needed. This study aims to analyze the relationship between crystalloid fluid pre-loading and blood pressure changes in patients with spinal anesthesia for cesarean section. A quantitative, analytical, observational study with a cross-sectional design was conducted on 51 patients from a population of 58 at Dr. R. Goeteng Taroenadibrata Purbalingga Regional General Hospital (January-February 2026). Purposive sampling and the Slovin formula were selected. Data were collected through observation sheets and Drager NIBP monitors, and bivariate analysis was carried out using Fisher's Exact Test. The results showed that 76.5% received adequate pre-loading (10-20 ml/kgBW) with a hypotension incidence of 12.8% versus 66.7% in the inadequate group (p=0.001). The findings confirmed a significant relationship between adequate crystalloid pre-loading and blood pressure stability. Pre-loading of 10-20 ml/kgBW is recommended for elective cases to minimize the risk of hypotension.